2017
DOI: 10.1089/chi.2017.0007
|View full text |Cite
|
Sign up to set email alerts
|

The Brain-Derived Neurotrophic Factor Val66Met Polymorphism, Delivery Method, Birth Weight, and Night Sleep Duration as Determinants of Obesity in Vietnamese Children of Primary School Age

Abstract: The study suggested the significant association of delivery method, birth weight, night sleep duration, and BDNF Val66Met polymorphism, with obesity in Vietnamese primary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Steinsbekk et al (2017) also showed that fat mass and muscle mass were strongly associated with speci c eating behaviors [10]. Besides that, many other factors have been demonstrated that increase the risk of childhood obesity such as socioeconomic status [11], physiological, metabolic, and genetic factors [12,13]... Our study in 2017 suggested the signi cant association of delivery method, birth weight, night sleep duration, and BDNF Val66Met polymorphism, with obesity in Vietnamese primary school children [14].…”
Section: Introductionsupporting
confidence: 54%
“…Steinsbekk et al (2017) also showed that fat mass and muscle mass were strongly associated with speci c eating behaviors [10]. Besides that, many other factors have been demonstrated that increase the risk of childhood obesity such as socioeconomic status [11], physiological, metabolic, and genetic factors [12,13]... Our study in 2017 suggested the signi cant association of delivery method, birth weight, night sleep duration, and BDNF Val66Met polymorphism, with obesity in Vietnamese primary school children [14].…”
Section: Introductionsupporting
confidence: 54%
“…The remaining 393 articles were read in full, with 281 excluded: 120 did not meet the age criteria (5‐13 years); 8 were of clinical or nonfree‐living population groups; 8 did not measure weight status objectively; 68 did not analyze the association between sleep‐obesity; and 77 were excluded either due to being non‐English, not peer‐reviewed, review/meta‐analysis, duplicate data, or a conference abstract/other unpublished data. This left 112 articles deemed relevant and included in the analysis (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…The Ethics Committee of the National Institute of Nutrition approved this study No. 12-01/HĐĐĐ in 2011 [13].…”
Section: Subjects Of Studymentioning
confidence: 99%